2020
DOI: 10.20944/preprints202009.0421.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesenchymal Stem Cells as a Bio Organ for Treatment of Female Infertility

Abstract: Female infertility is a global medical condition that can be caused by various disorders of the reproductive system, including premature ovarian failure (POF), polycystic ovary syndrome (PCOS), endometriosis, Asherman syndrome, and preeclampsia. It affects the quality of life of both patients and couples. Mesenchymal stem cells (MSCs) have received increasing attention as a potential cell-based therapy with several advantages over other cell sources, including greater abundance, fewer ethical considerations, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 83 publications
(99 reference statements)
1
2
0
Order By: Relevance
“…In our study, a comparative analysis of the HE staining results between the elderly treatment and model groups showed that BMMSCs improved ovarian structure and promoted follicle regeneration. These results are consistent with these reported in previous studies on MSC treatment of ovarian structure destruction and functional decline [28,31,32]. Interestingly, a previous study demonstrated the presence of adult oogonial stem cells (OSCs) in the adult axolotl salamander ovary and showed that ovarian injury induces OSC activation and functional regeneration of the ovaries [33].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, a comparative analysis of the HE staining results between the elderly treatment and model groups showed that BMMSCs improved ovarian structure and promoted follicle regeneration. These results are consistent with these reported in previous studies on MSC treatment of ovarian structure destruction and functional decline [28,31,32]. Interestingly, a previous study demonstrated the presence of adult oogonial stem cells (OSCs) in the adult axolotl salamander ovary and showed that ovarian injury induces OSC activation and functional regeneration of the ovaries [33].…”
Section: Discussionsupporting
confidence: 92%
“…Mitochondria are transferred from stem cells to adjacent cells through tunnel nanotubes, formed by pro-inflammatory cytokines that drive skeletal rearrangement in stem cells. It has also been recently reported that inflammation-driven transfer of mitochondria from stem cells to oocytes may rescue oocyte quality and embryo development [ 67 , 68 ].…”
Section: Innovative Therapeutic Options For Poimentioning
confidence: 99%
“…For female, the application of MSCs is also an important method that effectively improves ovarian function due to their abilities of differentiation and restoring endometrial function [ 88 ]. Besides, human endometrial MSCs can differentiate into granulosa cells and improve the renewal of GSCs [ 89 ].…”
Section: Technical Improvementmentioning
confidence: 99%